Suitability Evaluation of a Selected Company for an LBO / Zhodnocení vhodnosti vybrané společnosti pro LBO - Kostelanská, Markéta; Škerlíková, Tatiana; Menzl, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
The main goal of the bachelor’s thesis is to determine whether the international company H&M is a suitable candidate for a leveraged buyout (LBO). The key aspects of an LBO, such as the deal financing, the value creation, and the history of buyouts, are mentioned. A great emphasis is put on the main goal of the thesis – the description of given characteristics of an appropriate LBO target. At each there are methods stated, explaining how to conclude on a point. The practical part describes the selected company and informs about its performance in recent years. Afterwards, the mentioned procedures are applied to assess the company’s eligibility for an acquisition by a private equity company. A conclusion is made in the end, to sum up all findings from the practical part.
Vedoucí práce: Tatiana Škerlíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses